Can transfers and complementary nutrition programming reduce intimate partner violence four years post-program? Experimental evidence from Bangladesh - Roy, Shalini; Hidrobo, Melissa; Hoddinott, John F.; Koch, Bastien; Ahmed, Akhter (University of Wisconsin Press, 2024)
Little is known about whether reductions in intimate partner violence (IPV) from transfer programs persist. Using a randomized controlled trial, we find that women in rural Bangladesh who received cash transfers with complementary nutrition programming (including group-based training, home visits, and community meetings) experienced sustained reductions in IPV four years after the program ended. Neither cash transfers alone, nor food transfers with or without complementary nutrition programming, showed sustained impacts on IPV. Evidence suggests that cash with complementary nutrition programming sustained IPV reductions through persistent increases in women’s bargaining power, costs to men of perpetrating violence, and men’s emotional well-being.